PbSrNd isotopic tracing of the influence of the Amazon River on the bottom sediments in the lower Tapajós River. (October 2016) - Medeiros Filho, Lucio C.; Lafon, Jean-Michel; Souza Filho, Pedro Walfir M.
Abstract: The isotopic signatures of PbSrNd in recent bottom sediments were used to investigate the hydrodynamics of the lower stream of the Tapajós River and its interaction with the Amazon River. Samples from the Tapajós River have Pb isotopic ratios (19.67 <  206 Pb/ 204 Pb < 20.02; 15.87 <  207 Pb/ 204 Pb < 15.91) different from those of the bottom sediments found downstream in the Amazon River (18.84 <  206 Pb/ 204 Pb < 18.94; 207 Pb/ 204 Pb ≈ 15.67). In the confluence zone, the ratios have intermediate values (18.69 <  206 Pb/ 204 Pb < 19.53; 15.65 <  207 Pb/ 204 Pb < 15.83). The sediments in the Tapajós River have lower ɛNd(0) (−21 < ɛNd(0)  < −19) values and more radiogenic isotopic Sr ratios ( 87 Sr/ 86 Sr ≈ 0.792) than those of the sediments from the Amazon River (ɛNd(0)  ≈ −9 and 0.712 <  87 Sr/ 86 Sr < 0.716). The isotopic data suggest that the Amazon River influences the sediments in the Tapajós River, but this influence is restricted to the confluence zone. Additionally, the concentrations of major and trace elements and the mineralogy of the sediments are in agreement with the isotopic data. We conclude that the accumulation of muddy sediments in the lower stream of the Tapajós River is a result of the influence of the Amazon River, which retains this discharge from its affluent thus generating favorable conditions for depositing the finer sediments coming from the Tapajós River without any significant contribution of sediments from the Amazon River itself. The values of ɛNd(0) and TDM and of 87 Sr/ 86 Sr ratio of the Tapajós River bottom sediments indicate that the source of the sediments is essentially the erosion of the Paleoproterozoic felsic units from the Tapajós (2.03–1.88 Ga) and Juruena (1.82–1.54 Ga) geotectonic provinces. Graphical abstract: Highlights: PbSrNd isotopes indicate origin and mixing of bottom sediments. Hydrodynamics and interaction of the Tapajós River with the Amazon River. Influence of the Amazon River on Tapajós River sediments limited to the confluence. Tapajós River channel sediments originate from Paleoproterozoic felsic rock erosion.